The Role of Motivation In Mediating The Influence of Human Relations and Discipline on Employee Performance At The Directorate of Port Ministry of Transportation - Kamil, Abdul Hakim; puspa, Tiara; Fauzi, Achmad (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of the study was: "The Role of Human Relations, Discipline towards Motivation in Improving Employee Performance at the Directorate of Port, Ministry of Transportation". This type of research is a quantitative descriptive study, the population of this study is employees in the Port Directorate of the Ministry of Transportation which amounts to 149 people. The sampling technique in this study used saturated sampling found in Non-Probability Sampling, then the sample used was 149 respondents. The analysis method in this study was carried out with a Structural Equation Model (SEM) based on Partial Least Square (PLS). The results showed that: There is a positive influence of human relations on employee performance. The absence of the influence of discipline on the performance of employees. There is a positive influence of motivation on employee performance. There is a positive influence of human relations on motivation. The presence of a positive influence of discipline on motivation. Motivation cannot mediate the influence of human relations on employee performance, Motivation can mediate the influence of discipline on employee performance.